Single cell analysis via mass cytometry of spontaneous intestinal perforation reveals alterations in small intestinal innate and adaptive mucosal immunity - Olaloye, Oluwabunmi; Eke, Chino; Jolteus, Abigail; Konnikova, Liza (Frontiers in Immunology, 2023)
Spontaneous intestinal perforation (SIP) is a poorly understood severe gastrointestinal complications of prematurity. Using mass cytometry time of flight (CyTOF) of small intestinal tissue from neonates with SIP compared to second-trimester fetal and full-term neonatal tissue, we demonstrate immune dysregulation in SIP. SIP mucosa had an expansion of ckit+ neutrophils, an influx of naïve CD4 and CD8 T cells, and a reduction of effector memory T cells. SIP T cells were characterized by reduced CCR6 and CXCR3 expression and increased interferon-gamma (IFNg) expression after stimulation. These findings suggest that previously unrecognized immune dysregulation is associated with SIP and should be explored in future studies.